Efektivitas Model Pembelajaran Treffinger terhadap Kemampuan Pemahaman Konsep dan Pemecahan Masalah Matematis Peserta Didik Kelas VII SMPN 24 Padang - Sepriyanti, Nana; Zulmuqim, Zulmuqim; Suryani, Suryani (Math Educa Journal, 2017)
This research was based on the conceptual understanding and problem solving mathematical ability of students which is still low. The purposes of this research are (1) to investigate the students’ conceptual understanding ability with 2013 curriculum and Treffinger model of mathematics learning are higher compared with learning on 2013 curriculum only. (2) To investigate students’ problem solving mathematical ability implementing 2013 curriculum and Treffinger model are higher compared with learning on 2013 curriculum only. This is a quasi experimental research with Randomized Control Group Only design. The research result shows that the average score of experiment class student’s mathematics conceptual understanding is 76.61. Meanwhile, the average score for the control class is 71.49 with tcount = 1.826 and ttable = 1.645, so tcount > ttable. It means that hypothesis is accepted. The average score of experiment class student’s problem solving ability is 75.42. Meanwhile, the average score for the control class is 70.80 with tcount = 1.748 and ttable = 1.645, so tcount > ttable. It means that hypothesis is accepted. Finally, it can be concluded that the conceptual understanding and problem solving mathematical ability of the students class VII SMPN 24 Padang by using 2013 curriculum and Treffinger model are higher compared with learning by using 2013 curriculum only.Keywords: Conceptual understanding, problem solving, Treffinger model, 2013 curriculum learning.